CLINICAL CASE OF PRIMARY HYPOTHYROIDSIS - Daminov, Abdurasul Taxirovich; Yuldoshev , Bobur; Murodullo, Ikromov; Naimova , Nilufar (Educational Research in Universal Sciences, 2024)
Due to the fact that the population of Uzbekistan lives in conditions of iodine deficiency. Hypothyroidism is one of the most common disorders of the functional state of the thyroid gland, which negatively affects the quality of life of people, which makes this clinical problem relevant for doctors of various specialties. Thyroid hormones (TG) regulate the rate of metabolic processes in the body, change the activity of the adrenergic system, affect peripheral vascular resistance, enhance glycogenolysis and glycogenesis with specific contrainsular activity. During the aging process, the dynamics of many processes in the thyroid gland change: the thyroid gland’s absorption of radioactive iodine and thyroxine secretion decrease, the metabolism and clearance of thyroxine slow down, as well as the peripheral conversion of thyroxine to triiodothyronine.